P53 and E7 expression status in human cervical carcinoma cell (HELA) treated with quercusinfectoria aqueous extract - Radzuan, Syazatul Aniza (Universiti Sains Malaysia, 2015)
The search for novel anticancer agents has moved from cytotoxic agents to biologically targeted agents (which are primarily antiproliferative) to avoid the traditional toxic effects of anticancer therapy and to develop more selective and effective agents. Inhibition of cancer cells growth is a hallmark for declining the cell proliferation status in the treatment of cancer. In this regard, herbals are more preferable for alternative agent to treat cancer. A plant gall, Quercus infectoria (QI) (manjakani) extract had been reported to have antiproliferative activity towards cervical cancer cell, Hela. However, its antiproliferative mechanism is remaining undiscovered. Therefore, the current study has utilized aqueous extract of Q. infectoria to investigate partial of antiproliferative mechanism demonstrated by previous study. The expression status of tumor suppressor protein p53 and human papilloma virus protein E7 treated samples were analyzed in this study. Preliminary study revealed the antiproliferative activity of the extract as I7.92± 0.42 pg/ml. This concentration was used to determine the morphological changes and nuclear fragmentation as hallmark of apoptosis by Hoechst stain. The protein expression of p53 and suppression of HPV-E7 both evaluated by Western Blotting method with respective different incubation time 24, 48 and 72 hours. Treated cells demonstrated the morphological changes and fragmented nuclear. The p53 proteins were expressed and HPV E7 was slightly suppressed. These results suggested that, QI aqueous extracts acted to suppress the Hela cells proliferation by induction of apoptosis with expression of p53 and suppression of HPV E7